Występowanie, kondycja i zagrożenia zimoziołu północnego w Puszczy Augustowskiej - Zawadzka, Dorota; Bednarek, Jerzy; Bednarek, Joanna; Mikitiuk, Artur; Piechowska, Dorota; Zawadzki, Grzegorz (Leśne Prace Badawcze, 2017)
The twinflower Linnaea borealis L. is a rare, boreal plant species that grows in coniferous forests and is partly protected in Poland. We studied its distribution and the condition of twinflower patches in the Augustów Forest (NE Poland) describing 22 twinflower patches in total. The following features were assessed: (1) patch area, (2) distance between individual twinflowers, (3) patch density, (4) intensity of flowering, (5) fruiting, (6) main accompanying plant species, (7) plant community structure, (8) species composition and age of the forest stands, (9) canopy cover of the forest stands, (10) existing and potential threats. In the northern part of the forest where suitable pine sites dominated, twinflowers were distributed irregularly and unevenly. Twinflowers in the Augustów Forest occur in relatively big areas with individual patches covering from 100 m 2 to 3000 m 2 , but most commonly 500–1000 m 2 . The mean distance to the nearest neighbouring twinflower was 1600 m (range from 250 m to 6035 m). This pattern of distribution and separating distance does allow for sexual reproduction within the studied forest stand and blooming was confirmed in 21 out of 22 patches. In four locations, intensive blooming with >50 flowers shoot/m 2 was observed. We did not observe a dependency of the flowering intensity on patch size. Despite the intensive and frequent flowering, as well as the presence of fruits, which were found in 15 patches, the twinflower reproduces mainly vegetatively. Twinflowers grew in 34–166 years-old pine-spruce stands with moderate canopy cover, but there was no relationship between the age of forest stands and the size of a flower patch. Plant species, which commonly occurred with twinflowers were: Vaccinium myrtillus , Calamagrostis arundinacea , Goodyera repens , Rubus saxatilis , Fragaria vesca , Pleurosium schreberi . Twinflower communities are threatened by invasive species in the forest understory in two locations only, while in the other locations no active protection is needed and the plants should rather be protected and monitored through multifunctional forest management. We emphasise the importance of the Augustów Forest for the twinflower in Poland, because about 10% of the Polish population grows in this forest complex.